Trends of change in precipitation and in drought susceptibility as assessed by thestandardized precipitation index (spi) in Northeast Portugal - Royer, Ana Caroline (2021)
Much of NE Portugal is an area of arid zones with moderate to severe susceptibility to desertification and drought. A single and coupled trend analysis of precipitation and SPI drought index was performed in six weather stations in NE Portugal (representative of the regional climate domains), over a seventy-year time series (1931-2000). Precipitation over the study period decreased at most stations, with a more pronounced trend in the wetter areas, whereas in the semiarid areas an increase in precipitation was found. As well as the frequency of months with severe and extreme drought, the frequency of dry and wet months increased when the SPI timescale increased (1 to 6 months) and when a more recent computation period is considered (1931-1960 to 1971-2000). The results highlight a tendency for precipitation extremes to occur in NE Portugal. The general development of trends in precipitation and drought reported in this study confirm a progressive severity in the susceptibility to desertification affecting NE Portugal